The Antecedents of Satisfaction and Its Consequences on Tourist Behavioral Intentions: A Literature Review - Wayan Ardani (AIBPM Publisher, 2019)
Tourist satisfaction is becoming an increasingly salient topic and has drawn significant attention from academics and practitioners as it is the key factor in winning market share in the tourism industry. The aim of this paper is to provide empirical guidance regarding factors that influence satisfaction and its consequences on customer behavioral intention in tourism based on a systematic literature review. It is expected that this study will provide a better understanding of satisfaction towards a tourist destination, then a marketing strategy can be composed and implemented in order to increase tourist satisfaction. This article can be a reference for future studies on satisfaction and customer behavioral intentions in tourism.